Soldier neural architecture is temporarily modality specialized but poorly predicted by repertoire size in the stingless bee Tetragonisca angustula. Issue 4 (23rd December 2021) - Baudier, Kaitlin M.; Bennett, Meghan M.; Barrett, Meghan; Cossio, Frank J.; Wu, Robert D.; O'Donnell, Sean; Pavlic, Theodore P.; Fewell, Jennifer H.
Abstract: Individual heterogeneity within societies provides opportunities to test hypotheses about adaptive neural investment in the context of group cooperation. Here, we explore neural investment in defense specialist soldiers of the eusocial stingless bee ( Tetragonisca angustula ) which are age subspecialized on distinct defense tasks and have an overall higher lifetime task repertoire than other sterile workers within the colony. Consistent with predicted behavioral demands, soldiers had higher relative visual (optic lobe) investment than nonsoldiers but only during the period when they were performing the most visually demanding defense task (hovering guarding). As soldiers aged into the less visually demanding task of standing guarding this difference disappeared. Neural investment was otherwise similar across all colony members. Despite having larger task repertoires, soldiers had similar absolute brain size and the smaller relative brain size compared to other workers, meaning that lifetime task repertoire size was a poor predictor of brain size. Both high behavioral specialization in stable environmental conditions and reassignment across task groups during a crisis occur in T. angustula . The differences in neurobiology we report here are consistent with these specialized but flexible defense strategies. This work broadens our understanding of how neurobiology mediates age and morphological task specialization in highly cooperative societies. Abstract : Workers of the stingless bee Tetragonisca angustula consist of defense specialist soldiers and minors. Soldiers have an overall higher lifetime task repertoire than minors and are also age subspecialized on distinct defense tasks. We found that soldiers had larger optic lobes than non‐soldiers but only during the period when they were performing the most visually demanding defense task (hovering guarding). Despite having larger task repertoires, soldiers had similar absolute brain size and smaller relative brain size compared to other workers, meaning that lifetime task repertoire size was a poor predictor of brain size. This work broadens our understanding of how neurobiology mediates age and morphological task specialization in highly cooperative societies.